Medical Instrumentation Quality Evaluation System - Ali, Omar Mohammed Abd; alhmad, Mohammed yahya ali; Fathi, Dalya Taha Ahmed; Hussein, Omaima Elias Khaleel (American Journal of Botany and Bioengineering, 2024)
We touched on the quality system for medical devices, and we visited some laboratories, and it became clear to us that the issue of quality of medical devices is neglected in some medical laboratories. And we found that the group that we mentioned are the basic devices for each laboratory, and most of the malfunctions that occur due to lack of experience in maintaining the device, lack of interest in it, and failure to maintain it. We found through our research that some analysts and engineers do not have sufficient knowledge to deal with these devices, so we wrote this research to be a simple and easy guide for them. To be their assistant to deal with these devices. We wrote the research to be a guide for using these devices, even if the user does not have enough experience.